Verbindungsaufgaben für Profis

  1. a) (9r – 7s) · (-2) + (3s + 4r) · (-5) =
    b) (x – 2y + 5z) · 4 – (3y – 2x – z) · 5 =
    c) 2 · [9a – 3b + (b – 5a) · 3] =
    d) [4e – (4f + 3e) · 5 + 20f] · 2 =

  2. a) a² · (a – b) + ab · (a + b) – b² · (a – b) =
    b) a² · (a + 2b) – b² · (6a + b) – 2ab · (a – 3b) =
    c) 4x² · (3x² – 2) + 2x² · (3x + 4) - 3x · (2x² + 1) =
    d) y · (2y³ – 3) – 2y² · (3y² – 5) – 9y · (y – 1) =
    e) (u – v) · (-u) + (u + v) · v – v · (2u – v) =

  3. a) (4a – 7) · (3a² + 4) – (6a² – 3) · (2a + 5) =
    b) (7x – 3y) · (2x – 1) + 3y · (2x – 1) =
    c) (3a – b) · (a + b) – b · (2a – b) =
    d) (4a – 3b) · (7c – d) – (-6a + b) · (-4c + 5d) =

  4. a) (x + 2)² + (x – 2)² =
    b) (y – 2x)² + (x + 2y)² =
    c) (a + b)² – (a – b)² =
    d) 3 · (x + y)² – 2 · (x – y)² =
    e) (a + 2b) · (a – 2b) – (a + 3b)² =
    f) (3x – y)² – (3x + y) · (3x – y) =
    g) (4a + 3) · (4a – 3) + (5 + a) · (5 – a) =
    h) (r – 10)² – (r – 5)² =

  5. a) 2xy² – x · [(x – y)² – (x – y) · (x +y)] =
    b) ab – [(a + b)² – (a – b)²] =
    c) a² – [(a – b)² + (a – b) · (a + b)] =
    d) 2xy – [(x – y)² – 2xy] =
    e) (2x + y)² – (x – 2y)² – 3 · (x + y) · (x – y) =
    f) (2x + y)² + (x – 4y) · (x + 4y) =

Last modified: Monday, 5 January 2015, 10:20 AM